MODEL ALIANSI UNTUK PENINGKATAN KUALITAS PEMBELAJARAN DAN PENYERAPAN KERJA ALUMNI - Bambang Waluyo; Sujarwo Sujarwo (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2017)
Finance and Islamic Banking Department at PNJ established in 2010, produces first graduates in 2014. The activities between Finance and Islamic Banking Department and external parties inclclude with Department of Finance and Islamic Banking in the training of trainers (ToT) for the teaching staff of Islamic banking with several institutions. The research objective is to produce a model PNJ alliances with stakeholders in the development of Islamic banking and finance department to improve the quality of learning and absorption of graduates in the working area. This research used descriptive qualitative approach. Model alliances to improve the quality of learning to do PNJ with BI, OJK, training institutions, the Islamic finance industry, other universities. Model alliance absorption of graduates in the working world can do between PNJ with the Islamic finance industry. The success of the alliance is determined by factors of Senior Management Commitment, Similarity of Management Philosophies, Effective and Strong Management Team, Frequent Performance Feedback, Clearly Defined, Shared Goals and Objectives, Thorough Planning, Clearly Understood Roles, Partner Selection, and the Communication Between Partners , Obstacles faced to forge alliances with Islamic banking is their placement requirements PNJ funds in the bank. PNJ should offer advantages in alliance with Islamic banking industry is to prepare graduates who are ready to work so that will reduce the cost of training for new employees.